A simple cultivar suitability index for low‐pH agricultural soils. Issue 1 (5th November 2020) - Fordyce, Simon; Jones, Clain A.; Dahlhausen, Sally J.; Lachowiec, Jennifer; Eberly, Jed O.; Sherman, Jamie D.; McPhee, Kevin E.; Carr, Patrick M.
Abstract: Planting wheat ( Triticum aestivum L.) cultivars that carry the aluminum (Al) resistance gene TaAlmt1 is a potentially lower cost alternative to lime applications in acidic agricultural soils. However, the relative importance of TaAlmt1 expression and adaptedness (to regional environmental conditions) for preserving grain yield in acidic soils is not well understood. Adaptation trials were established in low‐pH soils to compare lime‐amended (YL ) and unamended grain yield (YU ) among regionally adapted spring wheat cultivars with and without TaAlmt1 . Averaged across YL and YU (YAVG ), yield of adapted TaAlmt1 carriers was similar to adapted noncarriers ( p = .939) but greater than nonadapted noncarriers ( p = .024). Soil pH‐driven spatial heterogeneity appears to inflate yield coefficients of variation and the probability of committing type II errors in cultivar yield comparisons. Our results support the use of YAVG as a suitability index and decision support tool for cultivar selection in acid‐affected soils. Abstract : A simple cultivar suitability index (a) was developed to address complications arising from within‐field variability in soil pH and pH‐related yield loss (b) in wheat.